von Willebrand factor abnormalities in aortic valve stenosis: Pathophysiology and impact on bleeding - Casonato, Alessandra; Sponga, Sandro; Pontara, Elena; Cattini, Maria Grazia; Basso, Cristina; Thiene, Gaetano; Cella, Giuseppe; Daidone, Viviana; Gerosa, Gino; Pagnan, Antonio (Thrombosis and Haemostasis, 2011)
Acquired von Willebrand syndrome (AVWS) may complicate severe aortic valve stenosis, due to a reduction in the haemostatically more efficient large von Willebrand factor (VWF) multimers. This study was designed to analyse the relevance of VWF abnormalities and haemorrhagic diathesis in severe aortic valve stenosis. Forty-one consecutive patients undergoing valve replacement were investigated: seven had minor bleeding symptoms in their recent history; 10 (24.3%) had a reduced VWF collagen binding (VWF:CB) to VWF antigen ratio, and 33 (80.5%) had a decrease in large VWF multimers. The shortage of large multimers was not associated with any accumulation of small VWF multimers (apparently ruling out any increased VWF proteolysis), nor was there any increase in VWF propeptide, which excludes a shorter VWF survival. The risk of developing VWF abnormalities was higher in patients with rheumatic valve disease than in degenerative cases (p=0.025) and in valves with <50% of residual endothelial cells (p=0.004). Bleeders differed from non-bleeders in that they had a higher mean transvalvular gradient and a more marked decrease in large VWF multimers. VWF abnormalities did not exacerbate peri-operative blood loss, however – a finding consistent with the full correction of these VWF abnormalities, seen already on the first postoperative day and persisting for up to six months after surgery. According to the data obtained in our cohort of patients VWF abnormalities are common in severe aortic stenosis, particularly in cases of rheumatic valve disease, but loss of the largest multimers does not seem to cause clinical bleeding in most patients.
Keywords: Aortic valve stenosis; von Willebrand factor; large VWF multimers; haemorrhagic diathesis; acquired von Willebrand syndrome